Competency Analysis of Elementary School Teachers in the Implementation of Scientific Learning in the 2013 Curriculum - Ahmad Tantowi; Camila Fatah Suroyya; Ahmad Munadirin (Sekolah Tinggi Agama Islam An-Nawawi Purworejo, 2021)
Curriculum changes from the education unit level curriculum (KTSP) to the 2013 curriculum have an impact on the implementation of learning. The 2013 curriculum applies a scientific learning model with the design of observing, asking, trying, reasoning, and communicating. An important thing for teachers to be able to implement scientific learning competently. This study aims to analyze the competence of elementary school teachers regarding scientific learning in the 2013 curriculum and find out the teacher's obstacles in implementing scientific learning in the 2013 curriculum. The research uses a case study method with the subject of teacher research in several elementary schools in Kendal Regency. Data obtained through interviews. In analyzing the data, the researcher followed the way of Miles and Huberman which consisted of four activity lines, namely: data collection, data reduction, data display, and data conclusion. The results of the study indicate that conceptually, teachers understand scientific learning and its implementation well and competently, but there are some other teachers who are still in the process of adjusting to implementing scientific learning. This study also revealed that there were deficiencies in scientific learning in the 2013 curriculum.